Save or sacrifice the internal mammary pedicle during anterior mediastinotomy? - Efstratios Apostolakis; Nikolaos A. Papakonstantinou; Serafeim Chlapoutakis; Christos Prokakis (Annals of Thoracic Medicine, 2014)
Ligation and dissection of internal mammary vessels is the most under-estimated complication of anterior mediastinotomy. However, patients requiring anterior mediastinotomy may experience long survival that makes the development of ischemic heart disease throughout their life possible. Therefore, the un-judicial sacrifice of the internal mammary pedicle may deprive them from the benefit to have their internal mammary artery used as a graft in order to successfully bypass severe left anterior descending artery stenoses. We recommend the preservation of the internal mammary pedicle during anterior mediastinotomy, which should be a common message among our colleagues from the beginning of their training.